Selective formation of one- and two-dimensional arrayed InGaAs quantum dots using Ga2O3 thin film as a mask material - Hahn, CK; Park, YJ; Kim, EK; Min, SK; Jung, SK; Park, JH (AMER INST PHYSICS, 1998)
We report on the selective formation of InGaAs quantum dots (QDs) by molecular beam epitaxy. Nanoscale patterned Ga2O3 thin film deposited on the GaAs (100) substrate was employed as a mask material. Due to the enhanced migration effect of the group-III adatoms, such as Ga and In on Ga2O3 mask layer, the InGaAs QDs formed on the patterned substrate results in coalesced islands unlike those formed on the nonpatterned substrate. The estimation of the relative volume of the islands per unit area revealed that the desorption process as well as the migration of the Ga and In adatoms might occur on the Ga2O3 layer during the growth process, providing a good selective growth of self-assembled QDs. (C) 1998 American Institute of Physics. [S0003-6951(98)05043-8].
Keywords: MOLECULAR-BEAM EPITAXY; ELECTRONIC STATES; GROWTH; SPECTROSCOPY; SURFACES